2022
DOI: 10.1038/s41598-022-14426-0
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological characterization of SARS-CoV-2 variants in children over the four COVID-19 waves and correlation with clinical presentation

Abstract: Since the start of SARS-CoV-2 pandemic, children aged ≤ 12 years have always been defined as underrepresented in terms of SARS-CoV-2 infections’ frequency and severity. By correlating SARS-CoV-2 transmission dynamics with clinical and virological features in 612 SARS-CoV-2 positive patients aged ≤ 12 years, we demonstrated a sizeable circulation of different SARS-CoV-2 lineages over the four pandemic waves in paediatric population, sustained by local transmission chains. Age < 5 years, highest viral load, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
2
19
0
4
Order By: Relevance
“…Despite the low risk, the asymptomatic group with a high SARS-CoV-2 viral load may play a significant role in community-based viral transmission. On the contrary, patients aged < 5 years were characterized by a higher SARS-CoV-2 viral load in the nasopharynx than the adolescent population [ 42 ]. However, in this study, we did not find a significant difference in SARS-CoV-2 viral load in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low risk, the asymptomatic group with a high SARS-CoV-2 viral load may play a significant role in community-based viral transmission. On the contrary, patients aged < 5 years were characterized by a higher SARS-CoV-2 viral load in the nasopharynx than the adolescent population [ 42 ]. However, in this study, we did not find a significant difference in SARS-CoV-2 viral load in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that age <5 years, the highest viral load, and gamma and delta clades positively influence this local transmission. No correlations between COVID-19 manifestations and lineages or transmission chains are seen, except for a negative correlation between B.1.1.7 and hospitalization [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children have been less likely to be infected and develop severe disease by the original SARS-CoV-2 (Wuhan) strain compared to adults 1 – 3 . However, the combination of increased transmissibility of SARS-CoV-2 Delta and Omicron variants, increased population movement due to the easing of COVID-19 restrictions, and a higher vaccination rate in adults compared with children have resulted in rising COVID-19 cases among children 4 , 5 . Despite this, SARS-CoV-2 infections in children are mostly mild or asymptomatic.…”
Section: Introductionmentioning
confidence: 99%